2016
DOI: 10.48550/arxiv.1611.10097
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ontologies for Privacy Requirements Engineering: A Systematic Literature Review

Mohamad Gharib,
Paolo Giorgini,
John Mylopoulos

Abstract: Privacy has been frequently identified as a main concern for system developers while dealing with/managing personal information. Despite this, most existing work on privacy requirements deals with them as a special case of security requirements. Therefore, key aspects of privacy are, usually, overlooked. In this context, wrong design decisions might be made due to insufficient understanding of privacy concerns. In this paper, we address this problem with a systematic literature review whose main purpose is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 96 publications
(190 reference statements)
0
6
0
Order By: Relevance
“…): OOPS! is a webbased ontology evaluation tool 14 for detecting common pitfalls in ontologies. The COPri ontology was uploaded to the OOPS!…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…): OOPS! is a webbased ontology evaluation tool 14 for detecting common pitfalls in ontologies. The COPri ontology was uploaded to the OOPS!…”
Section: Discussionmentioning
confidence: 99%
“…In COPri, we differentiate between two types of threat: (1) Incidental threat that is a casual, natural or accidental threat that is not caused by a threat actor nor does it require an attack method. (2) Intentional threat is a threat that require a threat actor and includes a presumed attack method [14]. Threat actor is an actor that intends to achieve an intentional threat [19].…”
Section: The Copri Ontologymentioning
confidence: 99%
“…• Step 3. Conceptualization aims at deriving an ontol-2 A detailed version of the systematic literature review can be found at [39] ogy that consists of key concepts and relationships for privacy [37]. In [9], we have proposed a preliminary ontology consisting of 38 concepts and relationships, which has been extended to 52 concepts and relationships in [27].…”
Section: Validated Ontologymentioning
confidence: 99%
“…In this context, we have adopted two di erent techniques, namely questionnaire-based and scenario-based. These two techniques complement each other: the former has been adopted because it allows for collecting multiple stakeholders' requirements simultaneously, eliciting the actual stakeholders' requirements, and most importantly its flexibility in contacting the stakeholders; the latter has been chosen because it allows for interactively involving stakeholders during the requirements elicitation process, which is essential for privacy requirements due to the vague nature of such requirements [24]. The requirements elicitation activity is repeated twice, with the main purpose of eliciting more detailed privacy requirements in the second iteration and it is composed of three main sub-activities:…”
Section: Requirements Elicitationmentioning
confidence: 99%
“…Although several e orts have been made to clarify this concept by linking it to more concrete concepts such as secrecy, personhood, control of personal information, etc. [69], there is no consensus on the definition of these concepts or which of them should be used to analyze privacy [69,24]. This adds more complexity while eliciting, classifying, prioritizing, and validating privacy requirements.…”
mentioning
confidence: 99%